PENGARUH PENGGUNAAN MEDIA POSTER TERHADAP HASIL BELAJAR HAK ASASI MANUSIA PADA PELAJARAN PENDIDIKAN PANCASILA KELAS XI DI SMKN - Nuril Bedriya; Lailatul Mahmudah; Arwani Rahmawati (SOCIAL : Jurnal Inovasi Pendidikan IPS, 2026)
Pancasila education in vocational high schools is often hampered by low student engagement due to the abstract and monotonous delivery of human rights (HAM) material. This study focuses on testing the effect of using poster media on improving the learning outcomes of eleventh grade students. The research steps were carried out through a quantitative approach with a quasi-experimental method using a nonequivalent control group design involving class XI DKV 1 as the experimental group and XI DKV 2 as the control at SMKN 1 Omben. Important stages start from administering a pretest, implementing visual-based learning, to the final measurement through a posttest on thirty subjects. The quantitative research findings through a nonparametric test showed a significance value of 0.247 which is greater than the 0.05 level, indicating that the data did not have a statistically significant difference. Although descriptively the average rank of the experimental class reached 17.27 while the control was 13.73, the Wilcoxon test confirmed that the increase in the treatment group was not significant with a p-value of 0.139. The main conclusion confirms that the integration of posters into human rights material has not been proven effective in significantly improving student academic achievement in this study. This is influenced by the abnormal and heterogeneous distribution of data, necessitating innovation in more interactive digital learning media to strengthen understanding of democratic values ​​sustainably in the future.